1991
DOI: 10.1093/ndt/6.9.615
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Intracellular pH and Na/H Antiporter Activity in Uraemia and Type I Diabetes Mellitus

Abstract: The leukocyte Na/H antiporter has been studied in patients with end-stage renal failure on maintenance haemodialysis. Thirteen non-diabetic haemodialysis patients (CRF group) and eight haemodialysis patients with diabetic nephropathy (CRF-DM group) were investigated. Measurements were made using the pH-sensitive fluorescent dye bis (carboxyethyl) carboxyfluorescein (BCECF). The initial intracellular pH (pHi), intracellular buffering capacity, and Na/H antiporter Vmax (at pHi = 6.0) have been recorded in bicarb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…Our data are partly at variance with those of Poli de Figueiredo et al [4], who showed normal Na+/H + anti porter activity in nondiabetic uremic HD patients; how ever, they did find reduced Na+/H + antiporter activity in diabetic HD patients in comparison with nonuremic dia betic controls, indirectly confirming a depressing effect of uremia on Na+/H + exchanger activity. In another recent study there was an increase of both Na+/H + activity and protein density in red blood cells [23].…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Our data are partly at variance with those of Poli de Figueiredo et al [4], who showed normal Na+/H + anti porter activity in nondiabetic uremic HD patients; how ever, they did find reduced Na+/H + antiporter activity in diabetic HD patients in comparison with nonuremic dia betic controls, indirectly confirming a depressing effect of uremia on Na+/H + exchanger activity. In another recent study there was an increase of both Na+/H + activity and protein density in red blood cells [23].…”
Section: Discussioncontrasting
confidence: 55%
“…in the absence of HCO 3/CO2) was lower than normal in lympho cytes from HD patients. It is worth noting that also other investigations showing intracellular acidosis in uremia [4,5] were performed in peripheral lymphocytes kept in Hepes solution. Thus, it would appear that uremic cells are somehow unable to properly regulate pH; in the absence of the physiological buffer HCO3/CO2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pH: is known to vary within a cell, [31][32][33] and hence raise the question of whether different levels of acidity might differently affect intracellular BO21 color, as it is a pH sensitive chromophore. 34,35 Given that intracellular pH ranges from about 5 to 8, 33 the absorption spectra of 10µM BO21 in PBS with pH levels ranging from 5.15 to 7.94 was measured, relevant area ratios d1/d2 were calculated and results depicted in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…This is known to vary within a cell and hence raise the question as to whether different levels of acidity might differently affect the intracellular BO21 color, as it is a pH-sensitive chromophore. , Given that intracellular pH ranges from about 5 to 8, the absorption spectra of 10 μM BO21 in PBS with pH levels ranging from 5.15 to 7.94 was measured; relevant area ratio d1/d2 was calculated, and the results are depicted in Figure . As can be seen, except for a negligible decrease in its intensity (at high pH), the nature of BO21 absorption spectra is insensitive to the pH values within said range, a finding which is further strengthened by the constancy of ratio d1/d2 (Figure right panel).…”
Section: Results and Discussionmentioning
confidence: 99%